Magnetostriction reveals orthorhombic distortion in tetragonal Gd compounds - Betancourth, D.; Correa, V. F.; Facio, J.I.; Fernández J.; Vildosola, V.; Lora-Serrano, R.; Cadogan, J.M.; Aligia, A.A.; Cornaglia, P.S.; García D.J.; Correa, Víctor Félix (American Physical Society, 2019)
Fil: Betancourth, D. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina; Universidad Nacional de Cuyo; Argentina